Integrasi-Interkoneksi Ilmu: Studi Tentang Hukum Bisnis Syariah - Syamsul Anwar (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2014)
This article deals with the much-mentioned methodolocical approach at Sunan Kalijaga State Islamic University, i.e. integrationinterconection in science. In this article the writer explains the meaning of both terms integration and interconnection and how the two approaches are used in the the study and practice of Islamic business law. As far as comtemporary Islamic business law practice is concerned, the writer is of the opinion that this legal system has undergone a kind of transformation through integrating some norms, rules, and intitutions of various legal pratices in and with which conmtemporary Islamic law coexists in different Muslim countries. But, according to the writer, the process of integration does not happen haphazardly, but, on the contrary, through a deliberate process in which those materials are yielded to the sharia principles in such a way that they come out in the form of Islamic law. If two well-known Dutch scholars in the colonial period, Van Vollenhoven and Snouck Hurgronje, created the so-called reception theory to explain the applicability of Islamic law to Muslim Inlanders, it would be also apt to say that contemporary Islamic business law apply the converted reception theory to distinguish it from that proposed by the two Ductch scholars.